La inconstitucionalidad por omisión, la supremacía de la Constitución y la defensa de los derechos fundamentales - Benites Pereda, Jhonny Xavier (2019)
We are pleased to present for the study, analysis and critique of the legal community, the fruit of our research that has revolved around the legal institute of unconstitutionality by omission or unconstitutional legislative omission, of little doctrinal study at the national level. The purpose of this paper has been to determine the influence of the incorporation of unconstitutionality by omission through the jurisprudence of the Constitutional Court in the supremacy of the Constitution and the defense of fundamental rights, a purpose that has been achieved through the analysis of the judgments of the aforementioned constitutional justice body and the complementary doctrinal and legal study regarding the indicated legal institute. In this sense, in order to achieve this, the postulates of the Constitutional State of Law are based, among others, the constitutional supremacy and the effective enforcement of fundamental rights, as a parameter of control of the action and inaction of public authorities, one of them the legislative body. Following that line, as it has been verified that in the national constitutional legal system, unlike other States, the possibility has not been foreseen that the Constitutional Court will rule on the unconstitutional legislative omissions, issuing binding pronouncements that oblige the legislative body issue the omitted rules, if applicable; arose the concern to investigate this problem to show that even if the Constitution does not foresee this possibility, in these times - and in light of the postulates that the Constitutional State raises - it is necessary to introduce this mechanism of constitutional legal control so that the system of constitutional justice is more complete. The research was carried out in accordance with the universal method of science, that is, the Scientific Method; giving birth to the description of the problematic reality, the approach of the problem, the objectives, the hypothesis and executing the whole proposed program. In addition, the general methods of sciences have been used, which are the Deductive - Inductive, the Analytical - Synthetic, the Analogical or comparative and the Hermeneutic - dialectical method. The use of the latter allowed us to understand the object of study in a triple perspective: as a legal institute in itself, its systemic - structural connection within the entire legal system and its interconnection with the historical - social context in which it operates, which is the Constitutional State of Law. Also, the techniques used for the collection, processing and analysis of information were the following: Content analysis, consisting of the set of intellectual operations that allowed to study and analyze the information contained in documents (Constitutional Court rulings) in an objective manner , coherent and systematic, to understand its content, describe trends, compare them, evaluate their clarity, and reflect approaches or perspectives of the person who issues them, and; the signing, which allowed us to review the theoretical - doctrinal documentation directly linked to the unconstitutionality by omission, the supremacy of the Constitution and the defense of fundamental rights, which contribute to the sustenance of the research hypothesis. In addition to has used the methods. In this sense, the presentation of this work is divided into four parts, namely: Title One: Methodological Framework, which includes the background, justification of the problem, statement of the problem, hypothesis, variables and objectives; Title Two: Theoretical Framework, in which the topics of the Constitutional State of Law, Fundamental Rights, the Supremacy of the Constitution, Unconstitutionality by Omission are developed and, finally, a specific mechanism is proposed to face the problem of legislative omissions unconstitutional; Title Three: Material and Methods, where the object of study is specified, the source of data collection, methods, techniques and data collection instruments; Title Four: Development of the Research, in which the results are shown (the data obtained from the studied sample is shown in detail), the discussion of results (the data obtained is contrasted, confronted and discussed, making them coherent with our problem and objectives) and conclusions (the final postulates of the work are established and the verification of whether the stated objectives were achieved) and finally the recommendations and the annexes are concluded.